Efektivitas Pendanaan Kredit Usaha Rakyat dalam Pengembangan Usaha Dagang Rukun Jaya - Chintia Sari; Nanda Cecharia; Rizky Oktavian Ramadhan; Cynthia Eka Violita (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research analyzes the effectiveness of People's Business Credit (KUR) financing in facilitating the development of Rukun Jaya Trading Business, a micro, small, and medium enterprise (MSME) specializing in the processing of kupang skin into animal feed. The rationale for this study is grounded in the pivotal role that micro, small, and medium enterprises (MSMEs) play in the Indonesian economy, alongside the persistent financial constraints they encounter challenges that the People's Business Credit (KUR) program seeks to address as a government-backed financing initiative.The objective of this study is to assess the degree to which the People's Business Credit (KUR) contributes to the advancement of the enterprise. A descriptive qualitative methodology is employed, utilizing data collection techniques such as interviews, observations, and document analysis.The findings indicate that KUR financing has proven effective in enhancing working capital, improving operational efficiency, and strengthening the enterprise's capacity to fulfill its credit obligations all of which contribute to the achievement of sustainable business growth. The implications of this study are intended to offer strategic insights for business owners in making informed decisions, assist financial institutions in enhancing the effectiveness of KUR distribution, and support government efforts in designing more targeted and impactful policies for MSME development.